Cercosporiose progression in the agroforestry consortium coffee-rubber trees - Androcioli, Humberto Godoy; Morais, Heverly; De Oliveira Menezes, Ayres; Hoshino, Adriano Thibes; Androcioli, Leonardo Godoy [UNESP]; Caramori, Paulo Henrique (Universidade Estadual de Londrina, 2015)
Cercospora coffeicola is one of the primary diseases that affect coffee plants. Studies indicate that shaded coffee plants reduce the incidence of this disease and that the management of trees and coffee plants arrangement influence in the dissemination of cercospora. The objective of this study was to evaluate the incidence and severity of C. coffeicola at different distances from double rows of rubber trees (Hevea brasiliensis muell. arg.) at two different sunlight exposures (north and south). This study was conducted in Londrina, Parana, between 2008 and 2010, with adult plants of the IAPAR 59 cultivar (Coffea arabica L.) grown at a spacing of 2.5 m × 1.0 m. The distances between the double rows of rubber trees were 13, 16 and 22 m, compared to plants grown under full sun. The disease incidence was assessed monthly by using a non-destructive method. This analysis was conducted on coffee leaves from the third and fourth pairs of two plagiotropic branches, on eight plants per plot, with five replications. These data were used to calculate the area under the curve for the incidence of the brown eye spot. The highest disease incidence occurred in the coffee plants grown under full sun, whereas lowest disease occurred on plants located at up to two meters away from double rows of rubber trees. The incidence of Cercospora leaf spot increased with the distance from the double rows of rubber trees. The results demonstrate that the mapping of cercospora incidence in shaded coffee plants is essential to determinate the best spacing and plants arrangement.
Keywords: Cercospora coffeicola; Coffea arabica; Coffee shading; Hevea brasiliensis